Scalable Perovskite Quantum Dot Glass Nanocomposites for High-Efficiency Luminescent Solar Concentrators - Ilter, Emre; Ekim, Utku; Asadi, Elshan; Tsoi, Konstantin; Yerci, Selcuk; Ersundu, Miray Celikbilek; Ersundu, Ali Ercin (WILEY-V C H VERLAG GMBH, 2025)
Achieving 2050 climate targets requires scalable and efficient renewable energy solutions. Luminescent solar concentrators (LSCs) offer a promising approach for building-integrated photovoltaics (BIPVs) by harvesting and guiding sunlight to photovoltaic cells. While perovskite quantum dots (PQDs) are highly efficient luminophores for LSCs, their instability in polymeric and liquid matrices hinders real-world deployment. Glass nanocomposites (GNCs) provide a durable alternative, yet scalability and efficiency trade-offs remain underexplored. This study investigates CsPbBr3 PQD GNC LSCs across various sizes, addressing this gap. Standardized 2.5 mm-thick samples with surface areas from 1 x 1 to 5 x 5 cm2 are fabricated and Monte Carlo simulations extend predictions up to 1 m2. A record-high photoluminescence quantum yield (PLQY) of 97% is achieved for a reference sample, highlighting exceptional emission efficiency. The highest power conversion efficiency (PCE) of 3.17% is recorded for small-scale devices, declining to 0.38% at 5 x 5 cm2. Simulations predict retention of 0.30% for 1 m2 LSCs, demonstrating scalability. Efficiency losses plateau beyond a critical size, enabling upscaling without major performance degradation. These findings establish PQD GNC LSCs as durable, scalable, and high-performance materials for next-generation BIPVs, supporting net-zero energy goals.
Keywords: building-integrated photovoltaics; glass nanocomposites; luminescent solar concentrators; perovskite quantum dots; power conversion efficiency; NANOCRYSTALS; Chemistry; Science & Technology - Other Topics; Materials Science; Physics